REQUESTS IN FILMS AND IN EFL TEXTBOOKS: A COMPARISON - Fernández Guerra, Ana; Martínez Flor, Alicia (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Research in the field of interlanguage pragmatics has shown that foreign language learners’ grammatical and pragmatic competences do not always match, this can perhaps be due to a lack of appropriate pragmatic presentation in current EFL textbooks. Hence, there seems to be a necessity of bringing authentic discourse into the classroom. One of the possibilities could be using films as input to develop classroom tasks. In this paper we analyse and compare the type, strategy and frequency of requests in both textbooks and films, in order to realise whether they provide an adequate treatment of this pragmatic issue. Results show an insufficient, unreal, decontextualised, and pragmatically inappropriate use of requesting strategies in the EFL textbooks analysed. We therefore propose using scenes from films as an authentic and motivating type of material which provides instances of real use of language and presents different requests in contextualised situations.